2016
DOI: 10.1002/2016gl068945
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical properties of eddies in the California Current System

Abstract: The California Current System (CCS) has intense mesoscale activity that modulates and exports biological production from the coastal upwelling system. To characterize and quantify the ability of mesoscale eddies to affect the local and regional planktonic ecosystem of the CCS, we analyzed a 10 year‐long physical‐biological model simulation, using eddy detection and tracking to isolate the dynamics of cyclonic and anticyclonic eddies. As they propagate westward across the shelf, cyclonic eddies efficiently tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 45 publications
(129 reference statements)
7
42
0
Order By: Relevance
“…Furthermore, a combination of the aforementioned perspectives is required in order to describe the properties of biogeochemical tracers averaged over multiple individual eddies. In this study, we aim to assess the nitrate transports resulted from mesoscale variability by applying Reynolds decomposition method (McGillicuddy et al, ; Nagai et al, ); then we focus on quantifying the overall effects of CEs and ACEs by using an eddy‐centric perspective (Castelao, ; Chenillat et al, ; Gaube et al, ; Gaube & McGillicuddy, ) based on daily samples extracted from a 25‐year simulation generated with a three‐dimensional physical‐biological coupled model of the GS region. Our methods are described in section 2. In section 3, the simulated mean state of the nutrients field over the study area is presented, followed by a description of the time‐dependent nutrient flux variations distributed in the horizontal and vertical directions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a combination of the aforementioned perspectives is required in order to describe the properties of biogeochemical tracers averaged over multiple individual eddies. In this study, we aim to assess the nitrate transports resulted from mesoscale variability by applying Reynolds decomposition method (McGillicuddy et al, ; Nagai et al, ); then we focus on quantifying the overall effects of CEs and ACEs by using an eddy‐centric perspective (Castelao, ; Chenillat et al, ; Gaube et al, ; Gaube & McGillicuddy, ) based on daily samples extracted from a 25‐year simulation generated with a three‐dimensional physical‐biological coupled model of the GS region. Our methods are described in section 2. In section 3, the simulated mean state of the nutrients field over the study area is presented, followed by a description of the time‐dependent nutrient flux variations distributed in the horizontal and vertical directions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of studies and observations in the CCS and other EBUS, the ecological roles of coastal eddies in upwelling systems are poorly documented. Recent studies have shown that eddies in the CCS are responsible for the offshore transport of coastal, nutrient-rich water and the redistribution of biogeochemical components through advection and diffusion (Gruber et al 2011;Stramma et al 2013) reach similar conclusions in the Humboldt Current System; Chenillat et al 2016). However, the mechanisms of formation of such coastal eddies, and, perhaps, more importantly their capacity to trap and transport tracers, are poorly understood, mainly due to the difficulties of studying these features at sea.…”
Section: Introductionmentioning
confidence: 80%
“…From the kinematic analyses of eddy C01-2, we found that it (i) formed near shore, trapping shallow coastal waters from the northern CC and nutrient-rich coastal waters from the southern CUC, and (ii) traveled offshore for at least 6 months with limited exchange with surrounding waters. Mesoscale eddies, and in particular cyclonic eddies, are known to play a fundamental role in modulating the biology of upwelling systems (Moore et al 2007;Almazán-Becerril et al 2012;Stramma et al 2013;Chenillat et al 2015Chenillat et al , 2016. In-depth investigations of the effects of eddies on planktonic ecosystem dynamics were carried out for eddy C01-2 in Chenillat et al (2015).…”
Section: Biological Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the ability to transport physical properties over long distances away from their formation region, nonlinear mesoscale eddies [ Chelton et al ., ] can presumably transport upwelled water as well as its chemical and biological properties [ Nagai et al ., ] with their westward drifts. Indeed, eddy‐induced transport of nutrients from the nearshore environment to the open ocean may result in reduced biological production in EBCS [ Gruber et al ., ], while maintaining locally elevated production in the eddies' interior [ Chenillat et al ., ]. Mesoscale eddies can also impact the spatial variability of SST through other mechanisms, including current‐induced and SST‐induced Ekman pumping [ Gaube et al ., ].…”
Section: Introductionmentioning
confidence: 99%